Efficacy of Repetitive Transcranial Magnetic Stimulation (rTMS) in Inducing Weight Loss among Obese Filipino Patients: A Randomized Controlled Trial - Encarnacion, Margaret; Dampil, Oliver Allan; Damian, Ludwig; Doquenia, Maria Leila; Redondo-Samin, Divina Cristy; Woolbright, Mary Karen (Journal of the ASEAN Federation of Endocrine Societies, 2020)
<center> </center><center> </center><center>*Visual Abstracts prepared by Dr. Francis Xavier Mislang</center> Objective. To determine the efficacy of rTMS in decreasing body mass index (BMI) versus sham stimulation among obese Filipino patients. Methodology. This was a single-center, randomized, sham-controlled, single-blind, parallel group trial. Participants were 15-65 years old with BMI ≥30 kg/m2 and weight stable for 6 weeks. Participants were randomized to receive real rTMS or sham stimulation. Each underwent 4 sessions of stimulation over 2 weeks. Anthropometrics, total caloric intake (TCI), and VAS score for appetite were taken at baseline, 2, 4, 6, and 12 weeks. Results. A total of 31 patients were randomized with 15 to the treatment and 14 to sham stimulation completing treatment, with 2 lost to follow-up. A significant decrease in BMI was noted after 4 weeks from the start of rTMS in the treatment group, (0.6±0.6, p-value=0.001), with weight change of -1.3±1.3 kg (p-value=0.009), but was no longer observed at 6 weeks onwards. No severe adverse effects were noted. Conclusion. rTMS to the DLPFC effectively decreased BMI (0.6±0.6) and weight (-1.3±1.3 kg) from baseline to 4 weeks. At 6-12 weeks after rTMS however, there was no longer a significant difference, indicating that 4 sessions of rTMS may not be enough to produce a prolonged effect on weight loss.